TEACHING DIGITAL FORENSICS AND CYBER INVESTIGATIONS ONLINE : OUR EXPERIENCES - Elizabeth K. Hawthorne; Rose K. Shumba (European Scientific Journal, ESJ, 2014)
This paper describes our experiences of teaching cyber investigations and digital forensics online. Additionally, it discusses open source toolkits and remote virtual labs appropriate for teaching cyber investigations and digital forensics effectively in a distance education environment. Both faculty and student experiences as well as lessons learnt from teaching these courses online at the University of Maryland University College (UMUC) are covered.